The topological degree method for equations of the Navier-Stokes type - V. T. Dmitrienko; V. G. Zvyagin (Abstract and Applied Analysis)
We obtain results of existence of weak solutions in the Hopf sense of the initial-boundary value problem for the generalized Navier-Stokes equations containing perturbations of retarded type. The degree theory for maps A−g, where A is invertible and g is 𝒜-condensing, is used.